Strategi Layanan Bimbingan dan Konseling dalam Menangani Krisis Identitas pada Remaja Kelas VII di SMP Negeri 5 Cimahi - Eka Nasywa; Kamal Rizkqi Sya'bani; Tunu, Rachel Putriani; Muhammad Rezza Septian (Advice: Jurnal Bimbingan dan Konseling, 2025)
Adolescence is a critical developmental stage characterized by the search for identity and is vulnerable to identity crises. This study aims to examine the Guidance and Counseling (BK) service strategy in dealing with identity crises in grade VII students at SMP Negeri 5 Cimahi. The study used a qualitative approach with data collection techniques through observation, interviews, documentation studies, and literature studies. The results of the study showed that the identity crisis experienced by students was characterized by low self-confidence, confusion in determining interests and talents, and a tendency to withdraw from the social environment. BK teachers implemented various service strategies such as orientation services, information services, group guidance, reality counseling, and the use of psychological tests to help students understand themselves and increase self-confidence. In addition, the involvement of parents, subject teachers, and external parties are important supporting factors in handling cases. Despite challenges such as low student self-awareness and negative environmental influences, BK services at SMP Negeri 5 Cimahi are considered effective in helping students face identity crises and build positive self-identities.   Keywords: Identity Crisis, Adolescents, Guidance and Counseling